Fieldwork on animals living in extreme conditions as a source of biomedical innovation - Yvon Le Maho; Aurélie Tasiemski; Fabrice Bertile; Philippe Bulet (Science in One Health)
Most biomedical research on animals is based on the handful of the so-called standard model organisms, i.e. laboratory mice, rats or Drosophila, but the keys to some important biomedical questions may simply not be found in these. However, compared with the high number of molecules originating from plants in clinical use, and with the countless unique adaption mechanisms that animals have developed over the course of evolution to cope with environmental constrains, there is still few investigations on wild animals with biomedical objectives, and field studies are far fewer. A major limitation is insufficient funding, the main causes of which we analyze. We argue, however, that fieldwork is a key driver in generating new scientific knowledge as part of a One Health approach, by observing/documenting and understanding the diverse and largely unexplored biological processes evolved by animals adapted to unusual environmental conditions, which would be extreme conditions for humans. These conditions do not only refer to extreme temperatures, since lack of food or water, high pressures or lack of oxygen, are clearly extreme constraints. To conduct this research, there are serious limitations we propose to address. Specific techniques and methods are requested, not only to work in extreme environments, but also to minimize the ecological footprint of field work. The erosion of biodiversity is a major threat. The reduction of animal disturbance, a key issue, requires specific technologies and expertise. An ethical approach is requested, for the sake of transparency and to comply with the Nagoya Protocol on genetic resources. An interdisciplinary expertise and a meticulous planning are requested to overcome the field constraints and interface the associated laboratory work. We recommend focusing on the major threats to global human health today, which wild animals appear to resist particularly well, such as antibioresistance and diseases associated with lifestyle and senescence.